The doctrine of sanctity of life from Islamic perspective - Wan Muhammad, Ramizah; Alias, Fadhlina; Jahn Kassim, Puteri Nemie; Hussin, Nasimah (International Institute of Islamic Thought and Civilization (ISTAC), International Islamic University Malaysia (IIUM), 2016)
Muslims believe that only Allah swt has the ultimate will and power over life and death. Life is merely a gift and a loan entrusted to mankind until death takes place. It is therefore forbidden for any person to intentionally end a life; to do so would be to commit a grievous transgression against Allah. Islam holds life in the highest esteem to the extent that the duty to preserve life forms one of the core principles in maqasid al-shari’ah. Protection of one’s life includes taking care of one’s body, health and mind from that which would lead to harm and death. All lives are equally inviolable; Islam does not discriminate one’s life on the basis of nationality, race or religion. In order to ensure a just order that protects both individual and public interests at large, Islam prescribes certain legitimate situations where the dimensions of sanctity of life are qualified, for example, by permitting to end life in self-defence or in due course of law. There is thus a need to understand the wisdom behind the sanctity of life principle in Islam, not only by studying its importance, but also the overall scope in which it operates.